Effect of Aerobics Exercise on Self-Esteem in Iranian Female Adolescents Covered by Welfare Organization - Marzieh Hasanpour; Mansooreh Tabatabaei; Mousa Alavi; Vahid Zolaktaf (The Scientific World Journal)
Introduction. Deprivation of parents might decrease self-esteem (SE) and result in affective and social incompatibility. In this randomized control trial, we examined the effect of aerobics exercise on SE among female adolescents living with no natural family. Materials and Methods. The sample consisted of all female adolescents aged 13 to 19 years (n: 72) who were covered by Isfahan Welfare organization. Participants were assigned into intervention and control groups by matched random sampling. Intervention included 8 weeks of aerobics exercise. Coppersmith SE inventory was administered before and after intervention as well as after one month follow-up. Results. No significant difference was seen between pre-SE scores of intervention (32.7±8.4) and control (33.0±6.7) groups (t=.16, P=.87). A significant difference was obtained in post-SE scores (40.2±5.7 versus 34.7±6.8, t=3.58, P=.001) and in one month follow-up scores (36.4±5.2 versus 33.0±5.2, t=2.25, P=.03). Discussion. The results demonstrated a low level of pre-SE in both groups. However, a significant improvement was seen in posttest of intervention group which persisted even one month after intervention. It supports the use of aerobics for female adolescents deprived from family life.